How Presenteeism Shaped Teacher Burnout in Cyberbullying Among Students During the COVID-19 Pandemic - Ferreira, Paula da Costa; Barros, Alexandra; Pereira, Nádia; Marques Pinto, Alexandra; Veiga Simão, Ana Margarida (Frontiers in Psychology, 2021)
The pandemic caused by SARS-CoV2 has had an impact on the education sector, and its stakeholders, such as teachers who had to do remote work from their home, despite many constraints. These professionals tried to perform their teaching functions, despite having to deal with adverse situations, such as cyberbullying among their students, as well as their difficulties related to presenteeism and burnout. In this context, this study aimed to understand whether observing cyberbullying among students can be associated with teachers’ productivity loss due to presenteeism and burnout. This study also proposed to examine the role of productivity loss due to presenteeism in the relationship between observing cyberbullying situations among students and teacher burnout. A random sample of 1044 (Mage = 51.05, SD = 7.35; 76.6% female) middle school and high school teachers answered an inventory about their experience working at home during the COVID-19 pandemic, specifically with regards to cyberbullying incidents they observed among their students, their productivity loss due to presenteeism and their burnout levels. Results from structural equation modeling revealed that observing students engaging in cyberbullying situations was positively associated with productivity loss due to presenteeism and teacher burnout. Also, teacher’s productivity loss due to presenteeism mediated the relationship between observing cyberbullying incidents among their students and their burnout levels. Specifically, the effect of productivity loss due to presenteeism explained the effect of observing cyberbullying incidents on teachers’ burnout levels. These results are innovative and shed light on the importance of teacher well-being at their job in the midst of a pandemic, namely when they observe their students engaging in hostile situations, which may lead them to greater levels of burnout.